COMPARISON OF PROCALCITONIN AND HEMATTOLOGICAL RATIOS IN CORD BLOOD AS EARLY PREDICTIVE MARKER OF NEONATAL SEPSIS - Israr, Sadia; Hayat, Asma; Ahmad, Tariq Mahmood; Majeed, Numan; Naqvi, Sakeena Hussain; Tehseen, Saema (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the predictive value of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) with procalcitonin in cord blood.Study Design: Case control study.Place and Duration of Study: Study was conducted in Army Medical College and Pak Emirates Military Hospital Rawalpindi, Jul 2018 to Mar 2019.Methodology: Those mothers, having deliveries with early rupture of membranes (EROM), premature rupture of membranes (PROM), preterm, dai handled, meconium and failure of induction have been included. Total 60 neonates were included in this study. Nineteen neonates were taken as a continuous clinical unsteadiness with a clearly documented suspicion of sepsis and two neonatologists decided sepsis within 1-3 days of life. While remaining neonates were control who have no infection. Results: Laboratory values show there was a gross difference in mean values of case and control for white blood cell (WBC), platelets, neutrophil, platelet to lymphocyte ratio and procalcitonin with statistical significance except lymphocyte count and neutrophil to lymphocyte ratio. In combined ROC curve. The cutoff of procalcitonin was calculated to be 0.4ng/ml with an area under curve of 84.5%. Similarly, cutoff of neutrophil to lymphocyte ratio was determined to be 1.39 with an area under curve of 65.1% at sensitivity of 63% and specificity of 58.5%. Cutoff of platelet to lymphocyte ratio was determined to be 47.48 with an area under curve of 66.8% at sensitivity of 78.9% and specificity of 49%.Conclusion: Combined hematological markers neutrophil to lymphocyte ratio and platelet to lymphocyte ratio with procalcitonin in cord blood could be used as a simple, sensitive and predictive parameter for identifying neonates susceptible to sepsis.